Pregnancy Management After Bariatric Surgery. Issue 6 (June 2016) - Badreldin, Nevert; Kuller, Jeffrey; Rhee, Eleanor; Brown, Laura; Laifer, Steven
Abstract : Obesity is a source of major morbidity and mortality and is a growing concern worldwide. Maternal obesity is associated with increased maternal and fetal risks during pregnancy. Bariatric surgery has emerged as one of the most sustainable treatments for severe obesity and its comorbidities. Patients who have undergone bariatric surgery often experience drastic improvements in hypertension and diabetes. It is not surprising, therefore, that the incidence of bariatric surgery is increasing, particularly in women of childbearing age. In fact, many women undergoing bariatric surgery plan to become pregnant in the future. Bariatric surgery may have a beneficial effect on rates of fetal macrosomia, gestational diabetes, hypertension, and preeclampsia. Conversely, studies have showed that bariatric surgery may increase the risk of small for gestational age infants and preterm birth. Given its rising incidence, it is important that physicians be able to thoroughly and accurately counsel and treat patients who plan to, or do, become pregnant after bariatric surgery. Target Audience: Obstetricians and gynecologists, family physicians. Learning Objectives: After completing this activity, the learner should be better able to identify medical risks associated with obesity; educate patients regarding the risks and benefits of pregnancy after bariatric surgery; and identify the key aspects of management of pregnant patients who have undergone bariatric surgery.